Promoting Gender Equality through Architecture and Technology-Based Education: An Islamic Values Approach - Awaliyah, Dian Nafiatul (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS), 2025)
This paper explores the role of architecture and technology in promoting gender equality through education, framed within the context of Islamic values, to support the United Nations’ Sustainable Development Goals (SDGs). Gender equality, as a crucial aspect of SDG 5, is vital for achieving broader societal development and empowerment. The study examines how architectural design and technological innovations can foster inclusive spaces and educational platforms that support gender equity in both urban and rural contexts. The research methodology involves a qualitative analysis of case studies, focusing on Islamic educational institutions, community centers, and digital platforms that integrate Islamic teachings with modern technologies. Key findings indicate that architecture, when designed with gender-responsive principles, can provide equal access to resources and opportunities, particularly for women in marginalized communities. Moreover, technology-based educational tools, rooted in Islamic values, offer flexible and accessible learning environments that break traditional barriers, promoting gender equality in the educational sphere. In conclusion, architecture and technology, aligned with Islamic principles, can play a transformative role in supporting gender equality. These tools are essential for fostering an environment that empowers both women and men, contributing to the achievement of SDGs, especially in communities where gender disparity is prominent. The integration of gender-sensitive architectural design and technological innovations has immense potential to transform educational environments into spaces of inclusivity and empowerment. By combining gender perspectives, collaborative design processes, and technological advancements, educational institutions can address systemic barriers and create environments that reflect the diverse needs of their communities.